The Fluid-Structure-Thermal Performance Analysis of Gas Foil Thrust Bearing by Using Computational Fluid Dynamics - Xiaomin Liu; Changlin Li; Jianjun Du (Lubricants, 2022)
This paper presents a detailed three-dimensional (3D) thermo-elastic-hydrodynamic (TEHD) multi-physics model of the bump-type gas foil thrust bearing based on computational fluid dynamics (CFD). In this model, the moving mesh technology is applied in the fluid flow domain, and the new boundary condition of fully developed flow is applied at the inlet and outlet boundaries, which is consistent with the continuous property of fluid flow and has better convergence performance in CFD. The groove between pads is set as the symmetry boundary. The contact pairs with Coulomb friction and contact/separation behaviors are considered in the structure deformation and heat transfer. The simulation results indicated that the boundary pressure has a significant influence on the foil deformation. It also revealed the heat flux transfer path and temperature distribution in the gas foil thrust-bearing (GFTB) system.